Rural school children picturing family life - Naydene de Lange; Tilla Olivier; Johanna Geldenhuys; Claudia Mitchell (Perspectives in Education, 2012)
Rurality is an active agent and central to the lived experiences of children growing up on a farm and attending a farm school. It is a key to their everyday experiences, and influences family life, schooling and their future. Previous studies elsewhere in the world have explored the notion of childhood in rural contexts, but there is a dearth of similar research in South Africa, which has a vast section of the population living in rural areas and therefore a vast number of children attending school in rural areas. A farm school – a public school on private property - provides the context for this study’s exploration of children’s views of family life in a rural area. The data was obtained using drawing as a visual participatory methodology with 16 primary school children, aged between 6 and 10, both boys and girls, providing an insider local perspective on growing up on a farm in a rural environment. How do children picture their lives? What do these pictures tell about rural family life? How does this influence schooling? This paper reports the findings and makes critical recommendations for turning the tide for children in rural education contexts.